2009 International Conference on Advances in Recent Technologies in Communication and Computing 2009
DOI: 10.1109/artcom.2009.29
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Adhoc Networks with Different Multicast Routing Protocols and Mobility Models

Abstract: A mobile ad hoc network (MANET) is a network consisting of a set of wireless mobile nodes that communicate with each other without centralized control or established infrastructure. The mobility model should represent the realistic behavior of each mobile node in the MANET. Routing protocols for ad hoc networks are typically evaluated using simulation, since the deployment of ad hoc networks is still relatively rare. However, past evaluations of multicast routing protocols have utilized a single, simple Random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Paper by Malarkodi et al [27] gives a more detailed classification in four categories: temporal dependency, spatial dependency, geographic restriction and hybrid characteristic. In this paper, it emphasises that the results of simulative performance evaluation strongly depends on the models used.…”
Section: Related Workmentioning
confidence: 99%
“…Paper by Malarkodi et al [27] gives a more detailed classification in four categories: temporal dependency, spatial dependency, geographic restriction and hybrid characteristic. In this paper, it emphasises that the results of simulative performance evaluation strongly depends on the models used.…”
Section: Related Workmentioning
confidence: 99%
“…B. Malarkodi et al (2009) [2] the impact of different mobility models on Multicast Routing Protocols. The results showed that the throughput of ADMR is higher than of ODMRP at high mobility.…”
Section: Fig 2 Classification Of Manet Routing Protocolmentioning
confidence: 99%
“…However Ad-Hoc networks show great potential in situations where internet access is not a key requirement or infrastructure is not available; including disaster or military scenarios or in low power wireless sensor networks or vehicles which only need to communicate with each other [9]. This paper is structured as follows; Section II discusses the core requirements of a MANET routing protocol, Section III discusses MANET routing principles, Section IV investigates some of the earliest MANET routing protocols; DSR and DSDV as well as the impact of mobility models on simulations.…”
Section: Introductionmentioning
confidence: 99%